1997
DOI: 10.1046/j.1469-0705.1997.10050316.x
|View full text |Cite
|
Sign up to set email alerts
|

In utero lysis of amniotic bands

Abstract: Amniotic band syndrome is a sporadic condition that occurs in approximately 1:1200 to 1:15,000 live births and that may result in amputations, constrictions and other deformities of the fetus. Although some cases present with congenital anomalies that are beyond surgical repair, a selected group of fetuses may show isolated limb constriction. It has been speculated that, without treatment, amputation or severe dysfunction of the limb may occur. Despite these potential complications, surgical treatment for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 0 publications
2
77
0
15
Order By: Relevance
“…In two other cases uterine wall and intra-amniotic bleeding led to removal of the second port (which was being used for the fetoscope). In these two cases the amniotic bands were released successfully under ultrasound guidance 6 . Postoperative subchorionic bleeding and membrane separation, with amniotic fluid loss within the first 24 hours after surgery, seem to be directly related to this procedure 5,18 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In two other cases uterine wall and intra-amniotic bleeding led to removal of the second port (which was being used for the fetoscope). In these two cases the amniotic bands were released successfully under ultrasound guidance 6 . Postoperative subchorionic bleeding and membrane separation, with amniotic fluid loss within the first 24 hours after surgery, seem to be directly related to this procedure 5,18 .…”
Section: Discussionmentioning
confidence: 98%
“…These findings have been confirmed in both animal and human studies 3−9 . The first two cases of antenatal release of amniotic bands that were causing ischemia of the extremities were reported in 1997, and the outcomes suggested that the operation could result in significant functional improvement 6 . Since then, nine studies on in-utero treatment of ABS have been reported in the literature, with further support for the view that release of the bands may prevent intrauterine fetal death.…”
Section: Introductionmentioning
confidence: 99%
“…Much milder findings with a near normal limb appearance were noted when the band was released fetoscopically twenty-five days later. Others [47][48][49] reported fetoscopic release at approximately twenty weeks gestation in humans, with improvement in the appearance of the extremities. These reports do not advocate isolated fetoscopic release, as the risks of such intervention are high.…”
Section: Do Tight Bands Cause Constriction Rings?mentioning
confidence: 99%
“…30 In utero, with the use of obstetric ultra sound scan, amniotic bands can be seen as linear echoes floating in the amniotic fluid and connected to the foetal body. 31 In the index cases however, the diagnosis of ABS was missed by obstetric ultra sound scan done at 15 weeks and 26 weeks respectively.…”
Section: Discussionmentioning
confidence: 99%